FLEXIBLE TEACHING AND LEARNING IN THE FILIPINO PROGRAM: TOWARDS THE INSTITUTIONALIZATION OF BLENDED LEARNING IN HIGHER EDUCATION INSTITUTIONS (HEIS) - Rumusud, Michelle-Ann (International Journal of Arts, Sciences and Education, 2025)
With the advancement of the education system toward digitalization, changes and innovations have been rapidly embraced. In response, the researcher examined various components of blended learning to develop a foundational program in Filipino for its institutionalization in Higher Education Institutions (HEIs) in Region 02. This initiative aims to assist stakeholders by addressing the specific needs and demands of teaching and learning in a blended learning environment. This study covers the platforms and modalities used in blended learning, the challenges faced by stakeholders, as well as their adaptive mechanisms. The scope of this research is limited to selected students, and teachers, from chosen public and private universities in Region 02. A descriptive-analytical research design was employed, utilizing quantitative methods. The results from aspects of the analysis will serve as the foundation to effectively institutionalize blended learning in Filipino for HEIs in Region 02.